The dissolution of the monasteries : a new history - Clark, James G. (New Haven : Yale University Press, 2021)
Shortly before Easter, 1540 saw the end of almost a millennium of monastic life in England. Until then religious houses had acted as a focus for education, literary, and artistic expression and even the creation of regional and national identity. Their closure, carried out in just four years between 1536 and 1540, caused a dislocation of people and a disruption of life not seen in England since the Norman Conquest. Drawing on the records of national and regional archives as well as archaeological remains, James Clark explores the little-known lives of the last men and women who lived in England's monasteries before the Reformation. Clark challenges received wisdom, showing that buildings were not immediately demolished and Henry VIII's subjects were so attached to the religious houses that they kept fixtures and fittings as souvenirs. This rich, vivid history brings back into focus the prominent place of abbeys, priories, and friaries in the lives of the English people.
The legend of the cloister -- The religious profession -- A regular world -- The Tudor Reformation -- The King's commissions -- The challenge of conformity -- Punysshid, subprest and put downe -- Nothing endid -- Changes of habit -- The Old World and the New.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on October 21, 2021).
eBooks on EBSCOhost
Keywords: Monasticism and religious orders -- England -- History -- 16th century; Monasteries -- England -- History -- 16th century; England -- Church history -- 16th century; Secularization -- England; Reformation -- England; England -- Church history -- 1485-; Church and state -- England -- History -- 16th century; Great Britain -- History -- Tudors, 1485-1603.; Monachisme et ordres religieux -- Angleterre -- Histoire -- 16e siècle.; Angleterre -- Histoire religieuse -- 16e siècle.; Sécularisation -- Angleterre; Angleterre -- Histoire religieuse -- 1485-; Église et État -- Angleterre -- Histoire -- 16e siècle.; Grande-Bretagne -- Histoire -- 1485-1603 (Tudors); HISTORY -- Europe -- Great Britain -- Tudor & Elizabethan Era (1485-1603); Monasteries; Monasticism and religious orders; England; 1500-1599; Electronic books; Church history; History